UPAYA SURFAID INTERNATIONAL MENGATASI PENYEBARAN MALARIA DI KABUPATEN KEPULAUAN MENTAWAI TAHUN 2010-2015 - Ade Malayanti; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research will explain about the efforts made by SurfAid International in addressing the spread of malaria in the district Mentawai islands. District Mentawai islands is a malaria endemic area with the largest positive contributor to the case in the province of West Sumatra. The geography of the area is inaccessible with inadequate access and the lack of human resources lead to health problems, especially malaria in the Mentawai difficult to overcome. The study was obtained by reviewing the literature either from books, journals, theses, reports, and internet. In addition, the authors also conducted interviews and direct observation. In this paper, the author used the pluralist perspective that is supported by the theory of international organization, and the level of analysis using the group as one actor in international relations. In this paper the authors also used the concept of Third Generation NGO Strategies. This research indicated that efforts SurfAid in tackling the spread of malaria in the Mentawai is to implement the program of malaria free Mentawai (MFM) in two districts, namely districts Sikakap and the District of South Pagai (village matobek, Sikakap and Malakopak). Surfaid also cooperated with the Mentawai Health Department in the implementation of MFM.Keywords: SurfAid International, Malaria, effort, Malaria Free Mentawai.